2018
DOI: 10.3390/vetsci5020041
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Proteinase C1A Paralog Profiles Correspond with Phylogenetic Lineages of Pathogenic Piroplasmids

Abstract: Piroplasmid parasites comprising of Babesia, Theileria, and Cytauxzoon are transmitted by ticks to farm and pet animals and have a significant impact on livestock industries and animal health in tropical and subtropical regions worldwide. In addition, diverse Babesia spp. infect humans as opportunistic hosts. Molecular phylogeny has demonstrated at least six piroplasmid lineages exemplified by B. microti, B. duncani, C. felis, T. equi, Theileria sensu stricto (T. annulata, T. parva, and T. orientalis) and Babe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
(74 reference statements)
1
11
0
Order By: Relevance
“…It can be observed that these three N -glycosylation enzyme sets can be assigned to the piroplasmid lineage of Babesia s.s. (Clade VI, set i), the closely related lineages of T. equi and C. felis (Clades IV and IIIa, respectively, set ii) and the distantly related B. microti and Theileria s.s. (Clades I and V, set iii) [ 8 , 9 ]. Similar to what was recently reported for piroplasmid C1A cysteine proteases and rhomboid proteinases, this observation corroborates the currently recognized phylogeny of piroplasmids [ 15 , 16 ]. On the other hand, the differences observed in the N -glycosylation pathway between B. microti and Babesia s.s., and between T. equi and Theileria s.s., underscore the need to revise the taxonomic placement of these two piroplasmids within the Babesia and the Theileria genera, respectively, as has been put forward before [ 8 , 9 , 17 ].…”
Section: Resultssupporting
confidence: 92%
“…It can be observed that these three N -glycosylation enzyme sets can be assigned to the piroplasmid lineage of Babesia s.s. (Clade VI, set i), the closely related lineages of T. equi and C. felis (Clades IV and IIIa, respectively, set ii) and the distantly related B. microti and Theileria s.s. (Clades I and V, set iii) [ 8 , 9 ]. Similar to what was recently reported for piroplasmid C1A cysteine proteases and rhomboid proteinases, this observation corroborates the currently recognized phylogeny of piroplasmids [ 15 , 16 ]. On the other hand, the differences observed in the N -glycosylation pathway between B. microti and Babesia s.s., and between T. equi and Theileria s.s., underscore the need to revise the taxonomic placement of these two piroplasmids within the Babesia and the Theileria genera, respectively, as has been put forward before [ 8 , 9 , 17 ].…”
Section: Resultssupporting
confidence: 92%
“…Although R. haemaphysaloides is not a typical B. microti-transmitting tick, it has been suggested as a potential vector for this parasite in China [50]. These results coincide with the inhibition exerted by R. microplus cystatins on a B. bovis C1A cysteine protease and suggest the involvement of these enzymes in tick host-pathogen interactions [51] Interestingly, the phylogenetic analysis of C1A cysteine protease paralog profiles of piroplasmids of the Babesia, Theileria and Cytauxzoon genera corroborates the assignment of analyzed species into Clades I-VI according to their 18S rRNA gene sequences [27,52].…”
Section: Cysteine Proteasesmentioning
confidence: 52%
“…Okubo et al [ 37 ] proposed an essential role of CPs in the invasion of B. bovis to the host RBCs. Ascencio et al [ 39 ] reported that T. equi exhibited extreme expansion of C1A-CP paralogs, which might be functionally associated with the evolution of the schizont stage. However, the exact function of babesial CPs remains uncertain.…”
Section: Resultsmentioning
confidence: 99%